(untitled) (Bioresearch Communications, 2026)
The fisheries sector occupies a pivotal position in Bangladesh’s economy, livelihoods, culture, and nutrition. The current study aimed to explore the diversity in fish consumption and sociodemographic factors associated to fish intake among the Bangladeshi adult rural population. Data from the Bangladesh Integrated Household Survey (BIHS 2018-2019) was used for the current study. Data processing and statistical analysis was done using IBM SPSS version 31.0 and R version 4.5.1. Geometric mean (95% CI) was used to express average fish intake of the respondents and partial proportional odds model was used to explore the factors associated to fish intake among the adult population (age:19-59 years) of rural Bangladesh. Adults (19–59 years) have the highest average fish intake (males 46.47 g/day; females 38.63 g/day), exceeding adolescents (males: 41.04 g/day; females: 35.51 g/day), older adults 60+ (males: 41.75 g/day; females: 34.61 g/day), and children <10 (males: 21.29 g/day; females: 20.40 g/day). About 42 (forty-two) different species of fish consumption was observed among the Bangladeshi rural adults. The overall fish intake comprised 40.77% small indigenous fish species (SIS), 31.35% large indigenous species, 23.67% exotic species, and 4.22% crustaceans. Among adults (19–59 years), fish contributes very little to total energy, negligible to carbohydrates, and a meaningful share to protein ( 14%), underscoring its role as a protein-dense rather than energy- or carb-dense food. Sex, household size, division, and marital status were found to be significantly associated with fish intake thresholds (p < .05) from partial proportional odds model. These findings highlight the need for targeted nutrition-sensitive policies and equitable food system strategies to enhance access to diverse fish species, ensuring fish continues to play a vital role in improving dietary quality in rural Bangladesh. Bioresearch Commu. 12(1): 1991-2000, 2026 (January)